Communications Trend Radar 2022. Language awareness, closed communication, gigification, synthetic media & cybersecurity - Stefan Stieglitz; Ansgar Zerfaß; Daniel Ziegele; Sünje Clausen; Karen Berger (Academic Society for Management & Communication, 2022)
The COVID-19 pandemic has accelerated changes in almost all areas of society, creating new opportunities but also threatening the success of corporate communications. How can communication experts tell the important trends apart from the unimportant ones? A research team from Leipzig University and University of Duisburg-Essen has conducted a comprehensive trend study and identified the most relevant trends in management, society and technology. For 2022 the following trends will be relevant: Language Awareness, Closed Communications, Gigification, Synthetic Media, Cybersecurity – – Die Corona-Pandemie hat Veränderungen in vielen Bereichen der Gesellschaft beschleunigt oder verstärkt. Daraus ergeben sich neue Chancen, aber auch Gefahren für die Unternehmenskommunikation. Doch welche Themen sind wirklich wichtig? Ein Forscherteam der Universität Leipzig und Unviersität Duisburg-Essen hat eine umfangreiche Trend-Studie durchgeführt und die wichtigsten Trends in den Bereichen Management, Gesellschaft und Technologie identfiziert. Für 2022 sind das die folgenden Trends: Language Awareness, Closed Communications, Gigification, Synthetic Media, Cybersecurity.
Keywords: 650